Co-infections of respiratory pathogens and gastro-intestinal parasites in smallholder pig production systems in Uganda - Oba, Peter; Wieland, Barbara; Mwiine, F.N.; Erume, J.; Dione, Michel M. (Springer, 2023)
A cross-sectional study was conducted to identify factors for infections of pigs with key respiratory pathogens: porcine circovirus type 2 (PCV2), porcine reproductive and respiratory syndrome virus (PPRSv), Mycoplasma hyopneumoniae (M. hyo), Actinobacillus pleuropneumoniae (App), and gastrointestinal (GI) parasites in Uganda. A structured questionnaire was used to collect data on management practices associated with infections. Ninety (90) farms and 259 pigs were sampled. Sera were screened against 4 pathogens using commercial ELISA tests. The Baerman’s method was used to identify parasite species in faecal samples. Logistic regression was done to identify risk factors for infections. Results showed individual animal seroprevalence of PCV2 was 6.9% (95% CI 3.7–11.1), PRRSv 13.8% (95% CI 8.8–19.6), M. hyo 6.4% (95% CI 3.5–10.5), and App 30.4% (95% CI 24.8–36.5). The prevalence of Ascaris spp. was 12.7% (95% CI 8.6–16.8), Strongyles spp was 16.2% (95% CI 11.7–20.7), and Eimeria spp. was 56.4% (95% CI 50.3–62.4). Pigs infested with Ascaris spp. were more likely to test positive to PCV2, odds ratio (OR) 1.86 (CI 1.31–2.60; p = 0.0002). For M. hyo, infection with Strongyles spp. was a risk factor (OR 12.9, p < 0.001). Pigs that had Strongyles and Ascaris spp. Infections (ORs 3.5 and 3.4, p < 0.001 respectively) were likely to have co-infections. The model showed that use of cement, elevated floor, and limiting contacts with outside pigs were protective while using mud and helminth infestations increased risks of co-infections. This study provided evidence that improved housing and biosecurity are critical in reducing pathogen incidence in herds.